2012
DOI: 10.1111/j.1365-277x.2012.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Home enteral tube feeding in children with inherited metabolic disorders: a review of long‐term carer knowledge and technique

Abstract: The HETF techniques of caregivers of children with IMD declined over time. Caregivers need to understand that HETF, particularly in IMD, is a serious procedure associated with life-threatening risks. Poor HETF practices may cause feed contamination, incorrect feed concentration, feed intolerance, aspiration, peritonitis and even metabolic decompensation. HETF skills should be reassessed annually, with compulsory retraining if basic 'core' HETF competencies are not demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 9 publications
1
21
0
2
Order By: Relevance
“…If tube feeding is needed in the long-term, gastrostomy is recommended [172]. Enteral feed composition is usually complex, requiring an individualized protein and energy profile commonly consisting of separate (or combined) modules of sources of protein, fat, carbohydrate, vitamins and minerals.…”
Section: Methodology and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…If tube feeding is needed in the long-term, gastrostomy is recommended [172]. Enteral feed composition is usually complex, requiring an individualized protein and energy profile commonly consisting of separate (or combined) modules of sources of protein, fat, carbohydrate, vitamins and minerals.…”
Section: Methodology and Objectivesmentioning
confidence: 99%
“…Enteral feed composition is usually complex, requiring an individualized protein and energy profile commonly consisting of separate (or combined) modules of sources of protein, fat, carbohydrate, vitamins and minerals. It is essential that all caregivers administering enteral feeding receive professional instruction in safe feed production and that their feed preparation technique is reviewed on an annual basis [136,172-174]. …”
Section: Methodology and Objectivesmentioning
confidence: 99%
“…Where carers on-teach other family members, in order that carers can be partially relieved of the need to always undertake procedure(s), there may never be any formal professional assessment of the new carers' skills. Furthermore, continued adherence to professional directives cannot be assumed, as demonstrated by a series of annual studies which used a questionnaire and observation to assess carers' knowledge and safety in administering home enteral tube feeding for children with inherited metabolic disorders (Evans et al 2010(Evans et al , 2011(Evans et al , 2012. Each of these studies reported high levels of inadequate infection control and incorrect measurement of feed ingredients which could pose risks to the recipients (although no data were provided about actual harm having eventuated).…”
Section: Complex Home Care: Issues Of Safety and Responsibilitymentioning
confidence: 99%
“…Some knowledge was still lacking despite annual review—this included dangers or incorrect tube placement, correct position for night feeding, and feed ingredient storage. Poor HEN practices can lead to feed contamination, feeding intolerance, aspiration, peritonitis, metabolic decompensation, and poor growth 29 …”
Section: Long‐term Considerations In Henmentioning
confidence: 99%